REKONSTRUKSI EDUKASI: MELESTARIKAN ALAM PANDAWA MELALUI PENGOLAHAN SAMPAH PLASTIK - Ni Putu Devi Ary Santhi; Ni Putu Laras Purnamasari; I Kadek Juni Arta (Sewagati, 2025)
Plastic waste is an urgent problem that must be addressed immediately. Plastic not only damages the ecosystem, but also threatens human health if not handled properly. As one of the efforts to overcome problems related to plastic waste, the Fine Arts Education study program (PPSR) in collaboration with the Informatics Engineering study program at PGRI Mahadewa University, carries out good activities, namely Community Service (PKM) activities. The activity program carried out is the creation of a plastic recycling installation entitled "Educational Reconstruction" which is present as a creative and educational effort in processing waste. This PKM implementation is in series with the Culture Run Bali 2024 activities, which are organized by Vinda Creative Events at Pandawa Beach. Culture Run is a running activity accompanied by various exciting activities at every kilometer in order to protect the environment and support "zero emissions" in Bali while preserving the cultural beauty of the Island of the Gods to continue to be spread to the wider community in Indonesia. The Plastic Recycling Installation is a work of art as well as educational media related to alternatives in processing plastic waste into environmentally and health-friendly art products.